Learning to talk from birth to three - Higgins, Louise T. ([Leicester, Eng.] The British Psychological Society, 1988)
Deals with the language development from birth to three years. The beginning sounds and the babies attentiveness to sounds around them.
Keywords: Language acquisition; Language; Psychology; Education